Deconstructing workplace spirituality: revealing the dynamics of psychological conformity and compilation of authentic nourishers in spiritual nourishment - Noorani, Ibrahim (Journal of spirituality in mental health, 2025)
Workplace spirituality is a psycho-theological phenomenon understood generally as employees’ inner drive to connect with fellows at work and become mindful of one’s inner consciousness, while pursuing a purposeful work. However, there exists an inherent probability that what is promoted as workplace spirituality is truly a cloaked version of psychological conformity on part of the employees. The present study incorporates an argumentative analysis to deconstruct how workplace spirituality in its present form is more inclined toward material pursuits rather than spiritual nourishment. Moreover, the study also provides a compilation of authentic nourishers who, when cultivated thoroughly in the workplace, can be amenable toward spiritual flourishing. In addition to explaining the significance of number 17 amongst spiritual traditions, the paper explores 17 different fragments which are required for spiritual nourishment.